2021
DOI: 10.1007/s11160-021-09678-4
|View full text |Cite
|
Sign up to set email alerts
|

Warming world, changing ocean: mitigation and adaptation to support resilient marine systems

Abstract: Proactive and coordinated action to mitigate and adapt to climate change will be essential for achieving the healthy, resilient, safe, sustainably harvested and biodiverse ocean that the UN Decade of Ocean Science and sustainable development goals (SDGs) seek. Ocean-based mitigation actions could contribute 12% of the emissions reductions required by 2030 to keep warming to less than 1.5 ºC but, because substantial warming is already locked in, extensive adaptation action is also needed. Here, as part of the F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 156 publications
(211 reference statements)
0
15
0
Order By: Relevance
“…Marine extreme climatic events (ECEs), such as marine heatwaves, are increasing in intensity and frequency with climate change (Frölicher et al, 2018;Laufkötter et al, 2020;Oliver et al, 2018;Perkins-Kirkpatrick & Lewis, 2020). Recent reviews on the subject call for an effort toward better understanding of ECEs and their ecosystem consequences to improve their predictability, and support ecosystem-based management to maintain marine systems resilience (Holbrook et al, 2020;Trebilco et al, 2022;van de Pol et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Marine extreme climatic events (ECEs), such as marine heatwaves, are increasing in intensity and frequency with climate change (Frölicher et al, 2018;Laufkötter et al, 2020;Oliver et al, 2018;Perkins-Kirkpatrick & Lewis, 2020). Recent reviews on the subject call for an effort toward better understanding of ECEs and their ecosystem consequences to improve their predictability, and support ecosystem-based management to maintain marine systems resilience (Holbrook et al, 2020;Trebilco et al, 2022;van de Pol et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Methods for communication can include technological tools such as environmental dashboards, or computer and smartphone applications. These tools can provide information on the current status of marine ecosystems and the future threat of climate change (Melbourne-Thomas et al 2021 ; Trebilco et al 2021 , this issue) and economic activities (Novaglio et al 2021 , this issue) to these systems. They can provide information about ecological outcomes of government policies and link consumers to supply chains and sustainability information on products (Farmery et al 2021 , this issue), and ultimately provide steps that individuals can implement to contribute to positive outcomes for marine environments.…”
Section: Discussionmentioning
confidence: 99%
“…Where there was overlap between the challenges, this affected the level of detail we considered on those aspects of our challenge on safeguarding marine life, and we refer to those papers for additional insights and solutions. For a detailed articulation of potential actions to support mitigation of, and adaptation to, climate change in marine systems, please see Trebilco et al ( 2021 , this issue) and Melbourne-Thomas et al ( 2021 , this issue). Likewise, anticipated global trends in the demand for seafood and other products, such as energy and minerals, and the growth of activities to meet such demand will significantly impact the conservation of marine biodiversity and ecosystems into the future.…”
Section: Methodsmentioning
confidence: 99%
“…The papers in the Future Seas special issue each explored potential scenarios of sustainable futures that are theoretically achievable for a range of key challenges for a healthy ocean (and in line with achieving the SDGs) including issues relating to indigenous rights and access [4], climate change [26], biodiversity conservation [27] and species redistribution [28], food security [29], ocean literacy [30], pollution [31], feedbacks between human and ocean health [32], resource use [33,34], international relations [35] and ocean governance [36]. For each challenge, ‘drivers’—factors that had the potential to impact on the challenge in question, in the context of the SDGs, over the Decade of Ocean Science—were identified that could be influenced to achieve desirable outcomes [32].…”
Section: Introduction and Research Contextmentioning
confidence: 99%